Dual Palatal Perforation as a Consequence of Chronic Cocaine Abuse: A Case Report with Literature Review - Mukram Ali, Fareedi; Shaher Alqahtani, Ahmed; Mousa Bakri, Mohammed; Mattoo, Khurshid A; Ali Hezam, Asma; Mohamed Morsy, Mohamed Sobhy; Mohamed Saiid, Saiid Elshafey (Addicta: The Turkish Journal on Addictions, 2025)
Palatal perforation can be either congenital or acquired, both of which may be related to a disease. However, a rare occurrence of palatal perforation can be a direct consequence as an infrequent complication associated with chronic cocaine abuse that is snorted through the nasal cavity. Cocaine powder when lodged within the nasal epithelium can result in oronasal communication, which would subsequently lead food and drink to reflux and cause nasal speech. This article presents a rare and a unique case of a 41 years’ adult male patient with two palatal perforations in the hard palate induced by chronic cocaine abuse for last 6 years. The patient had developed serious and annoying dysfunction in swallowing and phonation. The patient was advised to discontinue use of cocaine before starting the definitive prosthetic treatment. A brief review of the literature is also presented that focuses on the etiopathogenesis, differential diagnosis, and treatment to shed light on its oronasal effects.